"I'm nobody's Mum in this university": The gendering of work around student writing in UK higher education. Issue 32 (March 2018) - Tuck, Jackie
Abstract: A number of recent studies have raised critical questions about the gendering of academic labour in the contemporary university as workplace. This paper focuses on gendering discourses of work around student writing which surfaced in an ethnographically oriented study of fourteen academic teacher participants based in six diverse UK Universities in a range of disciplines. I draw on study findings to show that work with undergraduate writing and writers is often understood through feminising discourses of 'care' which explicitly and implicitly invoke stereotypically female caring roles in ways which reflect and perpetuate the marginalised status of writing work and at the same time infantilise students. I argue that the reassertion of care as a core academic value is necessary to counter such feminising discourses because such a reassertion challenges an unhelpful dichotomous separation between academic knowledge-making on one hand, and student writing as a personal issue on the other.